2022
DOI: 10.1108/ijefm-07-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity, involvement, satisfaction and behavioral intentions: the case of an African-American cultural festival

Abstract: PurposeThe study investigates how cultural festival attendees’ familiarity and involvement may influence their overall satisfaction and future behavioral intentions towards the festival.Design/methodology/approachA path analysis is used to test the proposed model. The Sobel test is performed to determine the mediating role of attendee satisfaction on future behavioral intentions.FindingsAttendee familiarity positively and directly impacts attendee involvement. Attendee satisfaction mediates the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…3.2.1 Intention to attend. The majority of prior studies use a single item to measure consumers' intention to attend the event (Bakhsh et al, 2020;Mishra et al, 2022;Rivera et al, 2022). This question asks about the consumers' likelihood to attend.…”
Section: Methodsmentioning
confidence: 99%
“…3.2.1 Intention to attend. The majority of prior studies use a single item to measure consumers' intention to attend the event (Bakhsh et al, 2020;Mishra et al, 2022;Rivera et al, 2022). This question asks about the consumers' likelihood to attend.…”
Section: Methodsmentioning
confidence: 99%
“…Its popularity can be partly explained by the measurement's simplicity and practicality (Jin et al, 2015). Researchers and practitioners are keen to establish whether satisfied visitors are prone to return to a festival, indicating visitors' patronage (Rivera et al, 2022;Žabkar et al, 2010). This leads us to our third and final hypothesis: H3.…”
Section: Behavioral Intentionmentioning
confidence: 96%
“…A good many of the festival marketing literature has focused on understanding the factors influencing visitors’ attendance at festivals (Culha, 2020; Lee, 2019; Monterrubio, 2019). Within this area, there has been an overemphasis on (de)motivational factors linked to visitors’ attendance (Baker and Crompton, 2000; Cole and Chancellor, 2009; Lee, 2019; Monterrubio, 2019; Rivera et al , 2022; Song et al , 2014; Yoon et al , 2010), but minimal emphasis on visitors’ experience and subsequent behavior. This is surprising given that a festival’s practical design and delivery requires the consideration of experiential marketing principles (Williams, 2006).…”
Section: Theoretical Background Hypotheses and Proposed Research Modelmentioning
confidence: 99%
“…Choo et al, (2022) verified the moderation effects of involvement in the associations among perceived quality, satisfaction and loyalty in the food festival context [11]. Rivera et al, (2022) also demonstrated that in a cultural festival trip, visitor involvement is positively affected by familiarity, and satisfaction plays a mediating role in the association between visitor involvement and intention to continually consume this cultural festival product; that is, when tourists have a certain familiarity with a festival, if they are more satisfied with their involvement in the festival, they are more willing to participate in the festival [69]. In addition, the enduring involvement theory was applied in a study about craft beer and food festival, indicating that an enduring involvement is related to various factors (e.g., familiarity), it is a crucial antecedent for predicting festivalscape with four sub-dimensions (convenience, food/beverage quality, facility, and staff), festival satisfaction and loyalty [70].…”
Section: Moderating Role Of Visitor Involvementmentioning
confidence: 99%